2021
DOI: 10.1002/anie.202107118
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Anti‐Markovnikov Radical Hydro‐ and Aminooxygenation of Unactivated Alkenes Tuned by Ketoxime Carbonates

Abstract: A tunable photocatalytic method is reported for anti‐Markovnikov hydro‐ and aminooxygenation of unactivated alkenes using readily accessible ketoxime carbonates as the diverse functionalization reagents. Mechanistic studies reveal that this reaction is initiated through an energy‐transfer‐promoted N−O bond homolysis of ketoxime carbonates leading to alkoxylcarbonyloxyl and iminyl radicals under visible‐light photocatalysis, followed by the addition of alkoxylcarbonyloxyl radical to alkenes. By taking advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 87 publications
4
25
0
Order By: Relevance
“…Control experiments have demonstrated that both the photosensitizer and visible light were essential for this carboimination reaction. Based on these experimental results and previous reports, 10–12,19 a plausible energy transfer-driven catalytic cycle is outlined in Fig. 3.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Control experiments have demonstrated that both the photosensitizer and visible light were essential for this carboimination reaction. Based on these experimental results and previous reports, 10–12,19 a plausible energy transfer-driven catalytic cycle is outlined in Fig. 3.…”
Section: Introductionsupporting
confidence: 70%
“…Based on recent works from the groups of Glorius, 10 Cho, 11 Han 12 and Xia 13 on the use of oxime esters as the source of N-centred diaryliminyl radicals, we hypothesized whether or not such a method could be used to synthesize γ-amino acid Schiff bases (Fig. 1c).…”
Section: Introductionmentioning
confidence: 99%
“…12 Han's group achieved the anti-Markovnikov hydrooxygenation and aminooxygenation of inactivated alkenes by tuning the structure of oxime carbonates. 13 They obtained alkoxylcarbonyloxyl and iminyl radicals as the key intermediates generated from oxime carbonates. Huo, Bao and Yuan's group carried out an intermolecular two-component regioselective alkene-oxyimination reaction using easily available aryl carboxylic-acid oxime esters as bifunctional agents, thereby producing aryl carboxyl and iminyl radicals.…”
mentioning
confidence: 99%
“…1 We postulated that N-(acyloxy)phthalimides (1) might be coaxed into adding to olefins wherein visible light irradiation might provide the driving force to overcome thermodynamic limitations of direct hydration-type reactions. 2 Alkyl N-(acyloxy)phthalimides have traditionally been used as acylating reagents. Pioneering studies from Okada and Odo revealed their propensity to undergo one-electron reduction, followed by N−O bond fragmentation to release alkyl radicals following decarboxylation.…”
mentioning
confidence: 99%
“…Oxymercuration/reduction, hydroboration/oxidation, and Wacker oxidation/reduction can provide alcohols and ethers with varying levels of regiocontrol and efficiency . We postulated that N -(acyloxy)­phthalimides ( 1 ) might be coaxed into adding to olefins wherein visible light irradiation might provide the driving force to overcome thermodynamic limitations of direct hydration-type reactions …”
mentioning
confidence: 99%